Immune Responses of a Novel Bi-Cistronic SARS-CoV-2 DNA Vaccine Following Intradermal Immunization With Suction Delivery - Jeong, Moonsup; Kudchodkar, Sagar B.; Gil, Areum; Jeon, Bohyun; Park, Gee Ho; Cho, Youngran; Lee, Hyojin; Cheong, Mi Sun; Kim, Wonil; Hwang, Yun-Ho; Lee, Jung-Ah; Lim, Heeji; et al. (Frontiers in Virology, 2022)
SARS-CoV-2 is the third pathogenic coronavirus to emerge since 2000. Experience from prior outbreaks of SARS-CoV and MERS-CoV demonstrated the importance of both humoral and cellular immunity to clinical outcome, precepts that have been recapitulated for SARS-CoV-2. Despite the unprecedented rapid development and deployment of vaccines against SARS-CoV-2, more vaccines are needed to meet global demand and to guard against immune evasion by newly emerging SARS-CoV-2 variants. Here we describe the development of pGO-1002, a novel bi-cistronic synthetic DNA vaccine that encodes consensus sequences of two SARS-CoV-2 antigens, Spike and ORF3a. Mice immunized with pGO-1002 developed humoral and cellular responses to both antigens including antibodies and neutralized infection by a clinical SARS-CoV-2 isolate. Rats immunized with pGO-1002 by intradermal (ID) injection followed by application of suction with our GeneDerm device also developed humoral responses that included neutralizing antibodies and RBD-ACE2 blocking antibodies as well as robust cellular responses to both antigens. Significantly, in a Syrian hamster vaccination and challenge model, ID+GeneDerm-assisted vaccination prevented viral replication in the lungs and significantly reduced viral replication in the nares of hamsters challenged with either an ancestral SARS-CoV-2 strain or the B.1.351 (beta) variant of concern. Furthermore, vaccinated immune sera inhibited virus-mediated cytopathic effects in vitro. These data establish the immunogenicity of the SARS-CoV-2 vaccine candidate pGO-1002 which induces potent humoral and cellular responses to the spike and ORF3a antigens and may provide greater protection against emerging variants.